2003
DOI: 10.1016/s0886-3350(02)01525-0
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation for bullous keratopathy in eyes with poor visual potential

Abstract: Amniotic membrane transplantation was a safe, effective, and long-lasting treatment modality for intractable pain associated with chronic bullous keratopathy in eyes with poor visual potential. It can be an alternative to conjunctival flaps for the long-term management of patients with bullous keratopathy in whom corneal transplantation is not indicated. A comparison of the efficacy of AMT with that of other surgical procedures must be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 21 publications
4
55
1
2
Order By: Relevance
“…Primary failure might be due to more pronounced loss of LSCs. In agreement with a study by Espana 33 et al, we found that patients with bullous keratopathy had the highest success rate and the lowest recurrence rate. The recurrence rate was higher (44%) in our study as compared to previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Primary failure might be due to more pronounced loss of LSCs. In agreement with a study by Espana 33 et al, we found that patients with bullous keratopathy had the highest success rate and the lowest recurrence rate. The recurrence rate was higher (44%) in our study as compared to previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our results have demonstrated that cross-linking treatment of bullous keratopathy might in fact be a successful symptomatic treatment approach for bullous keratopathy and an alternative to other treatment modalities like bandage contact lens, anterior stromal puncture [3] , amniotic membrane transplantation [2] , conjunctival flaps or excimer laser phototherapeutic keratectomy [4] . All of these measures are usually only recommended in the setting of painful bullous keratopathy and limited visual potential or to bridge time for a corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Bullous keratopathy is one of the leading indications for penetrating keratoplasty [1,2] . The most important factor in the pathogenesis of bullous keratopathy is endothelial dysfunction leading to chronic corneal edema, stromal scarring, epithelial bullae and recurrent erosions [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…In another publication in 2015, Sui et al studied 21 eyes of 20 patients with bullous keratopathy and moderate pain was encountered pre-and postoperatively. They found that, postoperatively, 76% of the eyes experienced absolutely no pain, (25). These data suggest that AM plays an essential role in reducing the pain and the other subjective symptoms when the ocular surface has been damaged.…”
Section: Discussionmentioning
confidence: 92%